Association between gene and miRNA expression profiles and stereotyped subset #4 B-cell receptor in chronic lymphocytic leukemia. Issue 11 (2nd November 2015) - Maura, Francesco; Cutrona, Giovanna; Mosca, Laura; Matis, Serena; Lionetti, Marta; Fabris, Sonia; Agnelli, Luca; Colombo, Monica; Massucco, Carlotta; Ferracin, Manuela; Zagatti, Barbara; Reverberi, Daniele; et al.
Abstract : In this study we investigated specific biological and clinical features associated with chronic lymphocytic leukemia (CLL) patients carrying stereotyped BCR subset #4 (IGHV4–34) among a prospective cohort of 462 CLL/MBL patients in early stage (Binet A). All subset #4 patients ( n = 16) were characterized by the IGHV mutated gene configuration, and absence of unfavorable cytogenetic lesions, NOTCH1 or SF3B1 mutations. Gene and miRNA expression profiling evidenced that the leukemic cells of subset #4 cases showed significant downregulation of WDFY4, MF2A and upregulation of PDGFA, FGFR1 and TFEC gene transcripts, as well as the upregulation of miR-497 and miR-29c. The transfection of miR-497 mimic in primary leukemic CLL cells induced a downregulation of BCL2, a known validated target of this miRNA. Our data identify biological characteristics associated with subset #4 patients, providing further evidence for the putative role of BCR in shaping the features of the tumor cells in CLL.